The Vestibular Implant Input Interacts with Residual Natural Function - van de Berg, Raymond; Guinand, Nils; Ranieri, Maurizio; Cavuscens, Samuel; Khoa Nguyen, T. A.; Guyot, Jean-Philippe; Lucieer, Florence; Starkov, Dmitrii; Kingma, Herman; van Hoof, Marc; Perez-Fornos, Angelica (Frontiers in Neurology, 2017)
Objective: Patients with bilateral vestibulopathy (BV) can still have residual “natural” function. This might interact with “artificial” vestibular implant input (VI-input). When fluctuating, it could lead to vertigo attacks. Main objective was to investigate how “artificial” VI-input is integrated with residual “natural” input by the central vestibular system. This, to explore 1) whether misalignment in the response of “artificial” VI-input is sufficiently counteracted by well-aligned residual “natural” input, and 2) whether “artificial” VI-input is able to influence and counteract the response to residual “natural” input, to show feasibility of a “vestibular pacemaker”. Materials and methods: Five vestibular electrodes in 4 BV-patients implanted with a vestibular implant were available. This involved electrodes with a predominantly horizontal response and electrodes with a predominantly vertical response. Responses to predominantly horizontal residual “natural” input and predominantly horizontal and vertical “artificial” VI-input were separately measured first. Then, inputs were combined in conditions where both would hypothetically collaborate or counteract. In each condition, subjects were subjected to 60 cycles of sinusoidal stimulation presented at 1Hz. Gain, asymmetry, phase and angle of eye responses were calculated. Signal averaging was performed. Results: Combining residual “natural” input and “artificial” VI-input resulted in an interaction in which characteristics of the resulting eye movement responses could significantly differ from those observed when responses were measured for each input separately (p<0.0013). In the total eye response, inputs with a stronger vector magnitude seemed to have stronger weights than inputs with a lower vector magnitude, in a non-linear combination. Misalignment in the response of “artificial” VI-input was not sufficiently counteracted by well-aligned residual “natural” input. “Artificial” VI-input was able to significantly influence and counteract the response to residual “natural” input. Conclusion: In the acute phase of VI-activation, residual “natural” input and “artificial” VI-input interact to generate eye movement responses in a non-linear fashion. This implies that different stimulation paradigms and more complex signal processing strategies will be required unless the brain is able to optimally combine both sources of information after adaptation during chronic use. Next to this, these findings could pave the way for using the VI as “vestibular pacemaker”.